A Case Report on the Management of Nasa-Arsha (Filiform Wart) with Ksharakarma (AYUSHDHARA, 2025)
Tumors are the uncontrolled growth of cells. Every tissue has their growth limitation, beyond which they don’t grow. Ayurved treats the disease by balancing the different body parameters using natural resources. There are thirty-one types of nasal disease out of which, there are four types of Nasa-Arsha. The Nasa-Arsha, which are uncomplicated, new and having less symptoms can be treated with oral medications. But Nasa–Arsha, which are deeply spread, soft and elevated are best to treat with Kshara-karma. Kshara or alkaline cuts, destroys, promotes healing, coagulates and prevents recurrence. This property of Kshara was not only revealed by our ancient sages but they used the Kshara, prepared from herbal origin as medicine. Kshara are used as Paneeya (as liquid to drink) drug and as local application. Paneeya drugs are used for internal disease whereas the Kshara which are applied locally, destroys the diseased tissue, achieve coagulation and promotes healing. Here an attempt is made to apply Apamarga-Kshara in a case of Nasa-Arsha or filli form wart, which provides an eye-catching effect. There was no sign of recurrence after the treatment till now.